2005
DOI: 10.1111/j.1572-0241.2005.41610.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy and the Risk of Colorectal Cancer

Abstract: OBJECTIVES:Cholecystectomy has been implicated as a possible risk factor for colorectal cancer. However, the clinical evidence and the underlying mechanism for this association are still inconclusive. We conducted a population-based study to further clarify this association. METHODS:We conducted a retrospective cohort study among all patients aged 40 yr or older in the General Practice Research Database from the United Kingdom. We excluded patients with <1 yr of colorectal cancer-free database follow-up as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 31 publications
2
50
1
1
Order By: Relevance
“…The cohort study also found that the risk of CRC occurrence is increased by cholecystectomy (Schernhammer et al, 2003). Findings of another study also indicate that cholecystectomy is associated with an increased risk for colon cancer (Shao and Yang, 2005). Abnormal bile duct metabolism increases the gallstone formation, leading to an increased risk of CRC.…”
Section: Cholecystectomymentioning
confidence: 84%
“…The cohort study also found that the risk of CRC occurrence is increased by cholecystectomy (Schernhammer et al, 2003). Findings of another study also indicate that cholecystectomy is associated with an increased risk for colon cancer (Shao and Yang, 2005). Abnormal bile duct metabolism increases the gallstone formation, leading to an increased risk of CRC.…”
Section: Cholecystectomymentioning
confidence: 84%
“…42 A causal association has been supported by the mechanisms after cholecystectomy, which include a continuous bile flow into the bowel. 43,44 The predilection of the right-side colon has been suggested through a greater proximal colonic absorption of fecal secondary bile acids, 15 which have been considered carcinogenic for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…A history of chronic cholecystitis or cholecystectomy, chronic appendicitis or appendectomy, and chronic diarrhea also had higher sensitivity than HAP, indicating that these unique Chinese high risk factors can detect a larger number of advanced neoplasias. Some studies have found an increase in the risk of CRC following cholecystectomy for gallstones [21][22][23][24][25][26][27] . Cholecystectomy also influences the adenoma to cancer transition, ultimately predisposing to the development of CRC [28] .…”
Section: Discussionmentioning
confidence: 99%